Coaching the double knee bend - Brewer, C.; Stone, M. (coachesinfo.com, 2007)
Multi-joint, multi-muscle, high-force, high-velocity movements such as the clean and the snatch form the basis of most sports-specific training programmes. The most efficient pulling technique for both the clean and the snatch lift has been observed over time to be the double knee bend. Not only does this introduce a sudden forceful stretch-shortening cycle into the movement, but the unweighted position also reduces tension on the back (Brewer et al., 2005). This movement should be deliberately coached into athletes from the early stages of skill learning in order to ensure that athletes are utilising the most effective lifting techniques because of the coaching that they are receiving, rather than despite of it. This paper has identified the key components of the double knee bend movement, and demonstrated a series of technique drills that a coach can use to develop this movement in the novice lifter from the outset of learning.